2008
DOI: 10.1007/s10503-007-9067-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Actual and Expected Persuasiveness of Evidence Types: How Good are Lay People at Selecting Persuasive Evidence?

Abstract: Whereas there are many publications in which argumentation quality has been defined by argumentation theorists, considerably less research attention has been paid to lay people's considerations regarding argument quality. Considerations about strong and weak argumentation are relevant because they can be compared with actual persuasive success. Argumentation theorists' conceptions have to some extent been shown to be compatible with actual effectiveness, but for lay people such compatibility has yet to be dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
34
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 20 publications
4
34
2
Order By: Relevance
“…The study of persuasive evidence has focused on the extent to which types of data affect people's adherence to factual claims that describe (future) events, such as "Listening to classical music helps students to absorb a lot of knowledge in a short period of time". Four types of evidence have generally been compared: statistical and anecdotal evidence in most cases (see Reinard, 1988;Allen and Preiss, 1997), but also causal evidence (providing an explanation for the claim), and expert evidence (in which an expert underscores the claim) (e.g., Hoeken, 2001;Hornikx and Hoeken, 2007). In these comparisons, people Judge the probability of different claims, which are supported by different types of evidence.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study of persuasive evidence has focused on the extent to which types of data affect people's adherence to factual claims that describe (future) events, such as "Listening to classical music helps students to absorb a lot of knowledge in a short period of time". Four types of evidence have generally been compared: statistical and anecdotal evidence in most cases (see Reinard, 1988;Allen and Preiss, 1997), but also causal evidence (providing an explanation for the claim), and expert evidence (in which an expert underscores the claim) (e.g., Hoeken, 2001;Hornikx and Hoeken, 2007). In these comparisons, people Judge the probability of different claims, which are supported by different types of evidence.…”
Section: Introductionmentioning
confidence: 99%
“…In these comparisons, people Judge the probability of different claims, which are supported by different types of evidence. Research has shown that statistical evidence, which is based on a large number of cases, is generally more persuasive than anecdotal evidence, which is based on a small number of cases (see reviews by Allen and Preiss, 1997;Hornikx, 2005). Studies in this domain give us insights into what kind of data are most likely to change people's beliefs about the phenomena described in claims.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evolutionary psychologists inquire about the function and origin of our argumentative abilities (Mercier and Sperber,2ou). Cognitive psychologists open up the narrow range of arguments that has been the focus ofthe psychology of reasoning and model underlying psychological mechanisms (Corner, Hahn and Oaksford, 2ou;Hahn and Oaksford, 2007;Hoeken, Timmers and Schellens, 2012;Hornikx, 2008). A special issue 0Ï Thinking and Reasoning, the flagship journal ofthe psychology of reasoning, on the topic of argumentation bears witness to this growing trend (Hornikx and Hahn, 2012).…”
mentioning
confidence: 99%